2017
DOI: 10.26444/aaem/80920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metal Cd pollution on microbial activities in soil

Abstract: Weilin Shi, Xiying Ma. Effects of heavy metal Cd pollution on microbial activities in soil. Ann Agric Environ Med. 2017; 24(4): 722-725. doi: 10.26444/aaem/80920 AbstractHeavy metal contamination of soil occurs when heavy metals are introduced to soil through human activities, leading to the gradual deterioration of the ecology and environment. Microorganism activity reflects the intensity of various biochemical reactions in soil, and changes in it reflect the level of heavy metal pollution affecting the soil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…Heavy metals are released into the environment from both anthropogenic and natural sources; these elements are highly reactive elements and often at low concentrations are toxic. These can enter the soil and groundwater, bioaccumulate in food webs and adversely affect the biota . At the same time metals play a vital role in various physiological processes and are linked to biomolecules in organisms homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are released into the environment from both anthropogenic and natural sources; these elements are highly reactive elements and often at low concentrations are toxic. These can enter the soil and groundwater, bioaccumulate in food webs and adversely affect the biota . At the same time metals play a vital role in various physiological processes and are linked to biomolecules in organisms homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, Shi et al (2017) assessed the effects of Cd pollution on soil microbial activities, reporting that heavy metals adversely affected soil microbial respiration. Although the mentioned study indicated that soil heavy metals variably affected soil microbial activity, the obtained results indicated that at lower Cd concentrations, soil microbes became resistant to heavy metals [38]; this is in line with our findings. According to the results of the present study, although increased soil contamination with Pb reduced microbial population, soil microbial respiration remained higher compared to the control soil samples.…”
Section: Resultsmentioning
confidence: 99%
“…A number of workers [30][31][32][33] have reported that potentially toxic elements particularly cadmium, copper, and zinc can disrupt the microbiological equilibrium of soil. Disturbances of the biological balance of soil caused by the excess of potentially toxic elements might be attributed to the disruption of physiological functions, denaturation of proteins and destruction of cellular membranes of soil microorganisms [34][35][36].…”
Section: Effects Of Potentially Toxic Elements On Soil Microbial Actimentioning
confidence: 99%
“…Potentially toxic elements immobilize soil bacteria, while microbial metabolites enhanced the mobility of potentially toxic elements [37][38][39]. Potentially toxic elements in different quantities and forms in soils cause changes in the counts of microorganisms, microbial biomass and microbial activity [33,[40][41][42][43] via inhibiting microbial community diversity, particularly that of fungal groups i.e., Ascomycota and Chytridiomycota) in the large-size fractions, which mainly depends on heterogeneous SOC availability across the PSFs. Potentially toxic elements create abiotic stresses [37,38] by inducing disorders in the metabolism of the microorganism.…”
Section: Effects Of Potentially Toxic Elements On Soil Microbial Actimentioning
confidence: 99%